Trends and differences in sexual practices and sexually transmitted infections in men who have sex with men only (MSMO) and men who have sex with men and women (MSMW): a repeated cross-sectional study in Melbourne, Australia - Eric P F Chow; Marcus Y Chen; Mario Martin-Sanchez; Jane S Hocking; Catriona Bradshaw; Christopher Fairley; Jason Ong; Richard Case (BMJ Open)
Objectives In the 2010s, there has been an increase in sexually transmitted infections (STI) in men who have sex with men (MSM) in Australia, and since 2015 also in urban heterosexuals. Men who have sex with both men and women (MSMW) have characteristics that may differ from both men who have sex with men only (MSMO) and heterosexual men. We aimed to compare the sexual practices and the trends in HIV/STI positivity between MSMO and MSMW.Design Repeated cross-sectional study.Setting A sexual health centre in Melbourne, Australia.Participants MSM aged 18 years and above who attended the Melbourne Sexual Health Centre for the first time between 2011 and 2018. This includes 12 795 MSMO and 1979 MSMW.Primary outcome measures Demographic characterics, sexual practices and HIV/STI positivity.Results Compared with MSMW, MSMO were more likely to practice anal sex and to have condomless receptive anal sex with casual male partners, and less likely to have a current regular relationship. Over the 8-year period, there was an increase in condomless receptive anal sex with casual male partners for both groups (MSMO: from 46.2% to 63.3%, ptrend <0.001; MSMW: from 41.3% to 57.9%, ptrend=0.011). Syphilis positivity increased in MSMO (from 5.5% to 7.9%, ptrend=0.012) and MSMW (from 0.9% to 6.4%, ptrend=0.004) and HIV remained stable. Gonorrhoea increased among MSMO from 2011 to 2014 (from 6.7% to 9.6%, ptrend=0.002), and remained stable from 2015 to 2018. MSMO had higher odds of testing positive for gonorrhoea (adjusted OR (aOR) 1.36, 95% CI 1.13 to 1.64), chlamydia (aOR 1.39, 95% CI 1.16 to 1.67), syphilis (aOR 1.74, 95% CI 1.37 to 2.22) and HIV (aOR 4.60, 95% CI 2.43 to 8.70) than MSMW.Conclusions MSMW have overall lower condomless sex and lower HIV/STI positivity. In the last years, changes in sexual practices in MSM have affected both MSMW and MSMO leading to an increased STI risk.